Soil health assessment in the brazilian dryland region (Caatinga Biome) - Lima, Antonio Yan Viana (2022)
The Caatinga is an exclusively Brazilian biome present in the semiarid northeast, the most populated dryland worldwide, where more than 28 million people live. Climate factors (e.g., long periods of drought), and deleterious anthropic activities contribute to the soil degradation in the Caatinga biome. Overgrazing is the main cause of soil loss in this region, reducing soil health (SH), agricultural productivity, and soil functioning. However, the effects of soil degradation in SH remain poorly understood in the Caatinga biome. This study aimed to i) evaluate how SH has been studied in the Caatinga biome through bibliometric analyses, ii) evaluate chemical, physical, and biological parameters of the soil, and iii) validate the SMAF (Soil Management Assessment Framework) tool for the assessment of the effects of overgrazing and the grazing-exclusion on the health of soils affected by desertification processes in the Caatinga biome. The number of publications by year, most cited articles, main institutions, major journals, most used keywords, and international scientific collaboration among countries and authors were cataloged, through the search for the terms “soil quality" OR "soil health" AND "Caatinga" OR "Brazilian semiarid" in the Scopus® database. The assessment of the impact of management practices on SH was carried out in an experimental area of the effects of degradation on the Irauçuba Desertification Nucleus, Ceará State, where 3 areas with different managements were evaluated: i) Native vegetation (NV), ii) in advanced degradation process by overgrazing (DE), and iii) Restored (RE – grazing-exclusion for 21 years). Soil samples were collected (0-10 cm) in February/2020 (S1) and October/2021 (S2), totaling 54 samples (3 areas x 3 managements x 3 blocks x 2 seasons). Chemical (pH, sodium adsorption ratio, extractable K, and P), physical (bulk density), and biological (soil organic carbon, microbial biomass carbon, and β-glucosidase activity) indicators were analyzed. The results showed that SH research in the Caatinga biome is fragmented and incipient (only 39 publications were found), limited to studies of soil processes, and with low connectivity among institutions and researchers. The restored area (RE) increased soil health indicators, as follows: RE = NV > DE. The SH assessment showed bulk density and sodium adsorption ratio as limiting indicator to SH in DE, while soil organic carbon, microbial biomass carbon and β glucosidase activity showed a significant increase in RE. This work shows that grazing exclusion can recover SH from degraded areas to levels similar to those of the native vegetation, and the effectiveness of SMAF in assessing the SH of the Caatinga biome.